A Composite Hydrogel Containing Mesoporous Silica Nanoparticles Loaded With Artemisia argyi Extract for Improving Chronic Wound Healing - Xue, Leyi; Deng, Tewei; Guo, Rui; Peng, Lu; Guo, Junjun; Tang, Fang; Lin, Jingxia; Jiang, Sufang; Lu, Huijuan; Liu, Xusheng; Deng, Lili (Frontiers in Bioengineering and Biotechnology, 2022)
Chronic wounds are a major health problem with increasing global prevalence, which endangers the physical and mental health of those affected and is a heavy burden to healthcare providers. Artemisia argyi extract (AE) has excellent antibacterial and anti-inflammatory properties. In this research, we developed AE loaded composite hydrogel scaffold based on methacrylate gelatin (GelMA)/methacrylate hyaluronic acid (HAMA) and mesoporous silica nanoparticle (MSN) as sustained-release drug carrier vehicles for the treatment of chronic wounds. The presented GelMA/1%HAMA hydrogel possessed stable rheological properties, suitable mechanical properties, appropriate biodegradability, swelling, sustained-release AE capacity. In vitro antibacterial and cell experiments showed that the GelMA/HAMA/MSN@AE hydrogel had excellent antibacterial activity and biocompatibility and induced macrophages to differentiate into M2 phenotype. In vivo wound healing of rat full-thickness cutaneous wounds further demonstrated that the prepared GelMA/HAMA/MSN@AE hydrogel could significantly promote chronic wound healing by upregulating the expression of IL-4, TGF-β1, CD31, and α-SMA but downregulating the expression of TNF-α and IFN-γ and promoting M1-M2 macrophages polarization. Altogether, we believe that the GelMA/HAMA/MSN@AE hydrogel will have wide application prospects in healing chronic wounds.